Pengembangan Materi Pendidikan Akhlak Islami untuk Anak Yatim Piatu Tunanetra - Syamsul Muqorrobin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research aims to analyze the development of Islamic Moral Education Materials for Blind Orphans. The type of research used is literature review. Data retrieval techniques with documentation from journal data on Google Scholar. Data analysis technique using Systematic Literature Review. The research results of Developing Islamic moral education materials for blind orphans is a very important effort in building the character and morality of individuals who face the challenges of life without parents and who have limited vision. This educational material not only aims to strengthen Islamic values, but also specifically adapts learning methods to the needs of blind children, such as the use of hearing and tactile methods. Thus, this approach not only supports spiritual development, but also pays attention to aspects of children's independence and practical skills. Overall, the development of Islamic moral education materials for blind orphans aims to form individuals who are tough, empathetic, and able to face life with confidence even though they are faced with the physical limitations and social losses they experience.